1967
DOI: 10.1080/00288330.1967.9515189
|View full text |Cite
|
Sign up to set email alerts
|

A textural analysis of Wellington Harbour sediments

Abstract: Grain-size and carbonate analyses have been carried out on bottom sediment samples of Wellington Harbour. From grain-size parameters it was possible to establish a number of facies types and to outline sediment sources and directions of transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…1). Ralph & Hurley (1952), Johannesson (1955), Maxwell (1956), Brodie (1958), Skerman (1958), Hurley (1959), R. M. Cassie (1959, V. , Gilmour (1960), Wear (1965), Van der Linden (1967), and Ritchie (1970) have presented hydrological data for the harbour. These and the present observations provide a useful background for biological research and for planned developments such as reclamation within the harbour.…”
Section: Introductionmentioning
confidence: 96%
“…1). Ralph & Hurley (1952), Johannesson (1955), Maxwell (1956), Brodie (1958), Skerman (1958), Hurley (1959), R. M. Cassie (1959, V. , Gilmour (1960), Wear (1965), Van der Linden (1967), and Ritchie (1970) have presented hydrological data for the harbour. These and the present observations provide a useful background for biological research and for planned developments such as reclamation within the harbour.…”
Section: Introductionmentioning
confidence: 96%
“…The study site was shallow (7 to 9 m water depth) and relatively exposed to prevailing north-westerly winds. The extremely poorly sorted sandy sediment reported by Van der Linden (1967) for this area indicates a wind-driven high-energy wave regime. Preliminary diving examination of the study site revealed sandy sediment interspersed with small pebbles, whole shells and coarse shell fragments and some small boulders.…”
Section: Methodsmentioning
confidence: 79%
“…1) and those of Brodie (1958) suggest there is a return flow along the Eastbourne coast immediately before high tide. Van der Linden (1966) found gravel in the entrance to Wellington Harbour in 1964-65 but this was covered by medium fine sand in 1974-75 (Carter, in press). Divers inspecting the bottom have frequently found waves of 1 m amplitude in the gravelly sediment.…”
Section: Tidal Speedsmentioning
confidence: 97%